Ergonomics assessment of current aircraft passenger seat design against Malaysian anthropometry data - Ozve Aminian, Negin; Izzuddin Romli, Fairuz (International Journal of Engineering and Technology, 2018)
There have been many complaints from aircraft passengers regarding the cabin comfort level during flight. One of the main cabin aspects that influence the level of passenger comfort is identified as the passenger seat. In this study, the representative of the current aircraft seat design is evaluated against anthropometry data of Malaysians. This is done to establish whether there is any mismatch between the seat design and the anthropometry of the Malaysian passengers such that it contributes to the low cabin comfort experiences. Based on the findings, it can be generally concluded that the current aircraft seat needs to be better and more ergonomically designed to match with the Malaysian anthropometry in order to potentially provide more comfortability for the Malaysian aircraft passengers.Â